Comparação das respostas ao exercício entre dois testes do degrau incremental em pacientes com doença pulmonar obstrutiva crônica - Andrade, Carlos Henrique Silva de (2010)
Background: Step test has been used to assess physical capacity in chronic pulmonary diseases. Objective: To compare the metabolic, cardiovascular and ventilatory responses, at the peak of exercise, between two step test protocols: Chester step test (CST) and modified incremental step test (MIST); secondarily to correlate the Work (number of steps x weight, kg x 0.20) on CST and MIST with pulmonary function, metabolic, cardiovascular and ventilatory variables and perception of effort. Methods: Thirty-two patients with COPD (FEV1: 50.34  15.40% of predicted) underwent the CST and MIST at the same day, an hour apart. Both tests were performed on a single step (20 cm of high) and were externally paced by sonorous stimulus previously recorded on a CD. CST started with a rhythm of 15 steps/minute and increments of five steps were performed every two minutes, with a total time of ten minutes. MIST started with 10 steps/minute and increments of one step every 30 seconds until the tolerance limit. Results: There was no significant difference between the CST and MIST at peak exercise: VO2 (1.22  0.59 L/min vs. 1.24  0.55 L/min, respectively), VE/MVV (0.63  0.14 vs. 0.61  0.14), HR (85.69  12.66% vs. 84.66  12.85%, respectively) and SpO2 (87.28  6.64% vs. 86.56  5.62%, respectively). The duration of the test (241.16  123.35 s vs. 360.31  171.05 s, respectively) and total number of steps differed significantly between CST and MIST (76.88  50.62 vs. 103.38  60.00, respectively). In MIST, the Work was significantly correlated to FEV1 (r = 0.54), FVC (r = 0.45), VE (r = 0.72) and VO2 (r = 0.84). The Work performed on CST presented significant correlations with FEV1 (r = 0.60), FVC (r = 0.52) and VO2 (r = 0.90). Conclusion: The metabolic, cardiovascular and ventilatory responses at peak of exercise were similar between CST and MIST. However, the duration of the test and total number of steps were higher in MIST than CST. In both tests, the work performed was related to the pulmonary function and variables at peak exercise.